Fentanyl infusion test for herpes zoster-associated pain - MOTOYAMA, Yasushi; NOMURA, Yuki; MIZOBUCHI, Satoshi; OBATA, Norihiko; SATO, Hitoaki; UENO, Kyohei (Journal of Japan Society of Pain Clinicians, 2022)
Introduction: This study investigated the results of a fentanyl test to evaluate the efficacy of opioids and select a treatment regimen for patients with intractable herpes zoster-associated pain (ZAP). Method: We studied 71 patients who underwent a fentanyl test for ZAP between January 2015 and January 2021. Subjects with pain reduction of greater than 50％ on a numerical rating scale were considered to be sensitive to fentanyl. We examined the analgesic effects, side effects, and treatments for pain following the fentanyl test. Results: Fifty-five percent of patients in the acute phase, 65％ in the subacute phase, and 70％ in the chronic phase were sensitive to fentanyl. Ninety-three percent of sensitive patients were treated with opioids after the test. In 75％ of the non-sensitive patients, the prescription of opioids was discontinued. Conclusion: Fentanyl showed an analgesic effect in ZAP regardless of the disease duration after onset. In our institution, we determine the opioid treatment for ZAP according to the result of the fentanyl test.